2019
DOI: 10.1002/cam4.2542
|View full text |Cite
|
Sign up to set email alerts
|

MACC1 regulates PDL1 expression and tumor immunity through the c‐Met/AKT/mTOR pathway in gastric cancer cells

Abstract: BackgroundImmunotherapy and its mechanisms are being studied in a wide variety of cancers. Programmed cell death ligand 1 (PDL1) is associated with immune evasion in numerous tumor types. Here, we aimed to assess the relationship between metastasis associated in colon cancer‐1 (MACC1) and PDL1 and examine their effects on gastric cancer (GC) tumor immunity.MethodsThe expression of MACC1, c‐Met, and PDL1 in human GC tissues was first assessed using quantitative RT‐PCR (qRT‐PCR) and immunohistochemistry. We then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…And, there are about 100 genes associated with mTOR signal pathway. It is consistent with the report that c-Met/AKT/mTOR pathway activated by MACC1 (metastasis associated in colon cancer-1) contributes to the PD-L1 expression in gastric cancer cells and induces tumor growth in vivo (Tong et al, 2019). We found that H. pylori contributes to the activation of mTOR as well as the PD-L1 expression during H. pylori infection whereas PD-L1 were downregulated when UreB was depleted ( Figure S3C).…”
Section: Mtor Signal Pathway Mediated Ureb Induced Pd-l1 Expressionsupporting
confidence: 92%
See 1 more Smart Citation
“…And, there are about 100 genes associated with mTOR signal pathway. It is consistent with the report that c-Met/AKT/mTOR pathway activated by MACC1 (metastasis associated in colon cancer-1) contributes to the PD-L1 expression in gastric cancer cells and induces tumor growth in vivo (Tong et al, 2019). We found that H. pylori contributes to the activation of mTOR as well as the PD-L1 expression during H. pylori infection whereas PD-L1 were downregulated when UreB was depleted ( Figure S3C).…”
Section: Mtor Signal Pathway Mediated Ureb Induced Pd-l1 Expressionsupporting
confidence: 92%
“…At least, we found a direct interaction between UreB and the heat shock protein family of host cells, so a further research focused on HSP mediated pathogenic mechanism during H. pylori infection will be valuable. mTOR was reported to regulate the expression of PD-L1 in gastric cancer (Tong et al, 2019), vice versa, PD-L1 promotes the proliferation of HNSCC cells through mTOR (Zheng et al, 2019). UreB upregulated immunosuppressive molecular PD-L1 through mTOR but not PI3K/AKT.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that abnormal HGF/c-Met upregulation and activation are often observed in bladder cancer [30]. Studies have also found that metastasis associated with colon cancer 1 (MACC1) regulates PDL1 expression and tumor immunity in gastric cancer (GC) cells through the c-Met/AKT/mTOR pathway [31]. We hypothesized that CENPM may regulate the expression of c-Met, leading to the occurrence of HCC, and more related research is needed.…”
Section: Discussionmentioning
confidence: 98%
“…The early diagnosis and precise treatment for GC become an important medical and social problem [13]. GC is often occult-onset with no specific symptoms, and patients are often in the advanced stage at the time of diagnosis [14]. Moreover, GC has high metastasis, and traditional radiotherapy and chemotherapy have little effects [15].…”
Section: Discussionmentioning
confidence: 99%